Independensi, Komitmen Organisasi, Gaya Kepemimpinan, dan Pemahaman Good Governace Terhadap Kinerja Auditor - Sriyanto Sriyanto; Dista Amalia Arifah (MAKSIMUM, 2014)
This study aims to independence, organization comitmen, leadership, and corporate governance understanding on public sector auditor performance. Research used internal governance auditor which belong to BPKP representation of Jawa Tengah province as population. Sample used convenience sampling method. From 60 questionare, it was only 42 return questionare. The statistic method used to test on the research hypothesis is multiple regression. The result of these study show that : organization comitmen, leadership, and corporate governance understanding had effect on public sector auditor performance.Keywords : auditor, independence, organization comitmen, leadership.